UN PROYECTO DEL ARQUITECTO JUAN CAYETANO MORATA PARA EL MONUMENTO A LA MEMORIA DEL GENERAL MARTÍN DE LA CARRERA EN MURCIA - López Martínez, Mª Cruz (Imafronte, 1995)
The aim of this project, by architect Juan Cayetano Morata, a Lieutenant in the Infantry of the Royal Army, was to erect a monument in memory of Field Marshall Martín de la Carrera, who died on 26th February 1812 in calle San Nicolás while defending the inhabitants of Murcia against French troops. The monument was not finished owing to the lack of marble at the time. Only the initial stages of the work remain, together with an inscription in white marble next to calle San Nicolás, no. 14, where the historical event occured.